Assessment of three-dimensional trunk kinematics and muscle activation during cycling with independent cranks - Bourdon, E.; Mavor, M.; Hay, D. C. (Journal of Sports Science & Medicine, 2017)
Independent cranks (IC) are recently introduced bicycle cranks that are decoupled; therefore allowing each leg to pedal independent of the other. Despite this introduction, limited research has been conducted assessing biomechanical changes when cycling with IC. Therefore, the purpose of this study was to evaluate and compare trunk kinematics and surface electromyography (sEMG) during IC and normal crank (NC) cycling during a graded exercise test to volitional fatigue. Ten healthy, physically active men performed two tests (IC and NC) on a cycling ergometer on separate days. 3D motion capture data of the trunk and pelvis and sEMG of the latissimus dorsi, tibialis anterior, gastrocnemius lateral head, rectus femoris, vastus lateralis and the biceps femoris were collected bilaterally. The first 30 seconds (beginning) and the last 30 seconds (end) of each trial were analyzed with respect to external load (beginning vs end), crank type (IC vs NC) side (left vs right), and phase of the pedal cycle (push vs recovery). Mean load at volitional fatigue in NC (351 W) was significantly greater than IC (318 W; p < 0.001). As external load increased, there was a similar increase in spine flexion angle in the sagittal plane for both NC (8.2°) and IC (4.6°). The NC condition demonstrated significantly greater increase in muscle activation from the beginning to the end than the IC condition in the tibialis anterior, rectus femoris and biceps femoris in the push phase, and the rectus femoris and biceps femoris in the recovery phase. As IC demonstrated less increase in activation, they cause less variation in muscular contraction from beginning to end throughout the full pedal range of motion, yet do not alter gross trunk kinematics. Due to altered muscle activation patterns when cycling with IC, they are proposed as a potentially beneficial training tool to increase training diversity.